Strategi Guru dalam Pelaksanaan Bimbingan Belajar bagi Siswa Berprestasi Rendah di Madrasah Ibtidaiyah Muhammadiyah Balun dalam menghadapi Tes Kompetensi Akademik 2026 - Kristiyuana; Lukman Hakim (Sekolah Tinggi Agama Islam Muhammadiyah Blora, 2025)
The implementation of the Academic Competency Test (TKA) at the elementary school (SD) level requires the academic and mental readiness of grade VI students in facing the transition to the junior high school/MTs level. This study uses a qualitative approach with the type of field research at Madrasah Ibtidaiyah (MI) Muhammadiyah Balun. The research subjects include classroom teachers, core subject teachers, and low-achieving students in class VI. Data was collected through in-depth interviews and observations, and analyzed through the stages of data reduction, data presentation, and conclusion drawing by triangulating sources. The results of the study show that teachers' strategies in tutoring include early identification of students' learning difficulties, strengthening basic academic competencies through remedial and contextual learning, individual and small group learning assistance, habituation to dealing with the characteristics of foreign workers, and the use of digital technology as a learning support medium. The implementation of the strategy is supported by the commitment of teachers and emotional closeness to students, but still faces obstacles in the form of time constraints and the unavailability of structured tutoring programs. This study confirms that adaptive tutoring plays an important role in increasing the academic readiness of low-achieving students to face TKA 2026.